Good-freedom – reflections from the time of the pandemic and not only – an autoethnographic statement - Józefowski, Eugeniusz (Kultura i twórczość w czasach zarazy: Doświadczenie pandemii a aktywność artystyczna z punktu widzenia twórcy i odbiorcy, 2021)
The author of the article is a visual creator describing his creative activity during the pandemic period. He places it in the space of his previous achievements. It does so with the awareness of creating source material with the features of maximum authenticity in order to present such an autoethnographic study to other researchers. The text presents the artist’s creative process in a methodical way. The illustrations of the works are presented and a certain key to their reading is based on the extensive set of titles attached to the article.